Self-assembled lipid-based nanoparticles for chemotherapy against breast cancer - Liu, Shan (Frontiers in Bioengineering and Biotechnology, 2024)
Self-assembled lipid-based nanoparticles have been shown to have improved therapeutic efficacy and lower toxic side effects. Breast cancer is a common type of malignant tumor in women. Conventional drugs such as doxorubicin (DOX) have shown low therapeutic efficacy and high drug toxicity in antitumor therapy. This paper surveys research on self-assembled lipid-based nanoparticles by categorizing them under three groups: self-assembled liposomal nanostructures, self-assembled niosomes, and self-assembled lipid–polymer hybrid nanoparticles. Subsequently, the structural features and operating mechanisms of each group are summarized individually along with examples of representative drugs from each group.